2018
DOI: 10.1007/s12663-017-1078-8
|View full text |Cite
|
Sign up to set email alerts
|

Brain Injuries and Facial Fractures: A Prospective Study of Incidence of Head Injury Associated with Maxillofacial Trauma

Abstract: Background Presence of head injuries in patients with maxillofacial trauma is a lifethreatening condition. Prompt determination of head injury in these patients is crucial for improving patient survival and recovery. Hence, the need to know about the incidence of head injuries associated with maxillofacial trauma becomes an important aspect. Materials and Methods A total of 100 patients were included in the study. Patient with head injuries associated with maxillofacial fractures was accounted to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 27 publications
4
27
0
1
Order By: Relevance
“…Due to the innate biomechanics of the craniofacial bones, similar FF patterns can occur after a wide spectrum of traumatic forces, and so it is often times unclear what diagnostic tests are warranted in order to detect concomitant injuries and guide management decisions [2] There have been a limited number of studies comparing the differences in fracture patterns, concomitant injuries, and management of patients with FFs following an LEM or HEM event. Prior studies describing patient outcomes after a FF often grouped heterogeneous mechanisms of injury (MOIs) together when evaluating mortality rates, airway management needs, or rates of intracranial hemorrhage (ICH) [3][4][5][6][7]. Grouping together both high-energy and low-energy MOIs, however, risks missing potential differences in injuries and outcomes between the two groups.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the innate biomechanics of the craniofacial bones, similar FF patterns can occur after a wide spectrum of traumatic forces, and so it is often times unclear what diagnostic tests are warranted in order to detect concomitant injuries and guide management decisions [2] There have been a limited number of studies comparing the differences in fracture patterns, concomitant injuries, and management of patients with FFs following an LEM or HEM event. Prior studies describing patient outcomes after a FF often grouped heterogeneous mechanisms of injury (MOIs) together when evaluating mortality rates, airway management needs, or rates of intracranial hemorrhage (ICH) [3][4][5][6][7]. Grouping together both high-energy and low-energy MOIs, however, risks missing potential differences in injuries and outcomes between the two groups.…”
Section: Introductionmentioning
confidence: 99%
“…29 Other associated injuries were subarachnoid hemorrhage 13 (18.5%), subdural hematoma 13 (18.5%), extradural hematoma 10 (14.2 %), contusions 16 (22.8%) and pneumocephalus 11 (15.7%), a study done by Elbaih AH et al has shown that brain injuries are commonly associated injuries with maxillofacial trauma. 30,31…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of head injuries associated with maxillofacial trauma has been reported to be as high as 67% and the most frequent maxillofacial injury is the fractured mandible. [77] Upper facial dislocation and zygomatic–orbital–maxillary complex fracture significantly more often co-exists with skull, dura mater or cranial nerve injuries, and zygomatico-orbital fracture with the injuries of the brain. [78] The number of facial fractures has also been shown to be inversely related to GCS.…”
Section: Considerations For Specific Surgeriesmentioning
confidence: 99%
“…[78] The number of facial fractures has also been shown to be inversely related to GCS. [77] Early fixation of facial fractures is associated with better esthetic results. However, principles similar to those with long bone fractures apply in this situation and maxillofacial surgery can be delayed till optimization of ICP.…”
Section: Considerations For Specific Surgeriesmentioning
confidence: 99%